Migraine induction with calcitonin gene-related peptide in patients from erenumab trials - Casper Emil Christensen; Samaira Younis; Marie Deen; Sabrina Khan; Hashmat Ghanizada; Messoud Ashina (The Journal of Headache and Pain, 2018)
Abstract Background Migraine prevention with erenumab and migraine induction by calcitonin gene-related peptide (CGRP) both carry notable individual variance. We wanted to explore a possible association between individual efficacy of anti-CGRP treatment and susceptibility to migraine induction by CGRP. Methods Thirteen migraine patients, previously enrolled in erenumab anti-CGRP receptor monoclonal antibody trials, received CGRP in a double-blind, placebo-controlled, randomized cross-over design to investigate their susceptibility to migraine induction. A standardized questionnaire was used to assess the efficacy of previous antibody treatment. The patients were stratified into groups of high responders and poor responders. Primary outcomes were incidence of migraine-like attacks and area under the curve of headache intensity after infusion of CGRP and placebo. All interviews and experiments were performed in laboratories at the Danish Headache Center, Copenhagen, Denmark. Results Ten high responders and three poor responders were included. CGRP induced migraine-like attacks in ten (77%) patients, whereof two were poor responders, compared to none after placebo (p = 0.002). The area under the curve for headache intensity was greater after CGRP, compared to placebo, at 0–90 min (p = 0.009), and 2–12 h (p = 0.014). The median peak headache intensity score was 5 (5–9) after CGRP, compared to 2 (0–4) after placebo (p = 0.004). Conclusions Patients with an excellent effect of erenumab are highly susceptible to CGRP provocation. If an association is evident, CGRP provocation could prove a biomarker for predicting antibody treatment efficacy. Trial registration Retrospectively registered at clinicaltrials.gov with identifier: NCT03481400.